ASSESSMENT OF TOTAL PETROLEUM HYDROCARBON IN SEDIMENT ALONG THE PORT HARCOURT SHORELINE IN RIVERS STATE (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The contamination of marine and coastal environments by petroleum hydrocarbons is a significant environmental concern, particularly in regions with extensive oil exploration and production activities. This study aims to assess the concentration and distribution of total petroleum hydrocarbons (TPH) in sediment along the Port Harcourt shoreline in Rivers State, Nigeria. Sediment samples were collected from ten different locations along the Port Harcourt shoreline between January and June 2024. The samples were analyzed for TPH using gas chromatography-mass spectrometry (GC-MS). Physicochemical parameters such as pH, temperature, and organic carbon content were also measured. Data were statistically analyzed to determine the spatial distribution and potential sources of TPH contamination. The results indicated that TPH concentrations in the sediment samples ranged from 1.5 mg/kg to 12.8 mg/kg, with the highest concentrations observed near industrial discharge points and oil spill sites. The average TPH concentration was 6.4 mg/kg, exceeding the permissible limits set by environmental regulatory agencies. The spatial distribution pattern suggested that the primary sources of TPH contamination were petrogenic, originating from oil spills and industrial discharges. The physicochemical analysis showed a significant correlation between TPH levels and organic carbon content in the sediment. The study highlights the high levels of TPH contamination in the sediment along the Port Harcourt shoreline, posing potential ecological risks to marine life and human health. There is an urgent need for stringent regulatory measures and effective remediation strategies to mitigate the impact of petroleum hydrocarbon pollution. Continuous monitoring and public awareness campaigns are essential to protect the coastal environment and ensure sustainable development in the region.